The city as an entertainment machine - Clark, Terry N. (Research in urban policy ;, 2004)
People both live and work in cities. And where they choose to live shifts where and how they work. Amenities enter as enticements to bring new residents or tourists to a city. Amenities have thus become new public concerns for many cities in the US and much of Northern Europe. Old ways of thinking, old paradigms - such as "location, location, location" and "land, labour, capital, and management generate economic development" - are too simple. So is "human capital drives development". To these earlier questions, we add: "how do amenities and related consumption attract talented people, who in turn drive the classic processes which make cities grow?" This new question is critical for policy makers. Urban public officials, business, and nonprofit leaders are using culture, entertainment, and urban amenities to (seek to) enhance their locations - for present and future residents, tourists, conventioneers, and shoppers. This volume explores how consumption and entertainment change cities. But it reverses the "normal" causal process. That is, many chapters analyse how consumption and entertainment drive urban development, not vice versa. It details the impacts of opera, used bookstores, brew pubs, bicycle events, Starbucks' coffee shops, gay residents and other factors on changes in jobs, population, inventions, and more. It interprets these processes by showing how they add new insights from economics, sociology, political science, public policy, and geography. Considerable evidence is presented about how consumption, amenities, and culture drive urban policy - by encouraging people to move to or from different cities and regions. The book also explores how different amenities attract the innovative persons who are catalysts in making the modern economy and high tech hum.